DESIGN OF BIOGAS PURIFICATION TO REDUCE CARBON DIOXIDE (CO2) AND HYDROGEN SULFIDE (H2S) - Kardo Rajagukguk; Arysca Wisnu Satria (Universitas Bandar Lampung, 2019)
Biogas is a gas produced from decomposition of organic matter by microorganisms in anaerobic conditions. The problems that are mainly from the development of biogas technology are the high levels of H2S and CO2 in biogas which become an obstacle in the application of biogas directly because it can lead to corrosive components of energy conversion equipment (generator sets) and can reduce the heating value in biogas combustion. The aim of the paper is to design a biogas purification device using Calcium Hydroxide Ca(OH)2, Iron Oxide (Fe2O3), Zeolite, and Activated Carbon in the biogas which are designed according to the characteristics of the biogas installation in Indonesia. From experimental results the percentage of methane gas content increased from 52.5% to 90.2% after purification. Ca(OH)2 solution can be used for adsorbent to increase methane gas levels and reduce CO2 levels in biogas. Fe2O3 iron powder can be used to reduce the levels of H2S content in biogas so that it can increase methane gas content and is safe to use on generator engines.Zeolite and Activated Carbon can increase methane gas levels and reduce the moisture content and CO2 contained in the biogas so that when the biogas is applied to the generator engine. The power generated in the generator engine using biogas fuel that has been purified is greater than that which has not been purified